Bis(2-methoxyethyl)ether promoted intramolecular acceptorless dehydrogenative coupling to construct structurally diverse quinazolinones by molecular oxygen. Issue 4 (1st February 2022) - Zhao, Rongrong; Wen, Simiaomiao; Fu, Hao; Liu, Mengna; Liu, Qixing; Zhou, Haifeng
Abstract : A simple, efficient and clean intramolecular oxidative dehydrogenative coupling for the synthesis of dihydroisoquinolino[2, 1- a ]quinazolinones, 2-aryl quinazolinones, and analogues promoted by bis(2-methoxyethyl)ether/O2  has been achieved. Abstract : A simple, efficient, and clean approach for the synthesis of diverse dihydroisoquinolino[2, 1- a ]quinazolinones, 2-aryl quinazolinones, and analogues through intramolecular acceptorless dehydrogenative coupling has been achieved. The combination of bis(2-methoxyethyl)ether and molecular oxygen was identified as a highly efficient system for this oxidative dehydrogenative coupling sequential transformation without an external initiator, catalyst, and additive. The applicability and practicability were demonstrated by a scope of twenty-nine examples and a gram-scale reaction. Some control experiments were also conducted to support a possible reaction pathway.